Near‐infrared fluorescence imaging to facilitate super‐selective arterial clamping during zero‐ischaemia robotic partial nephrectomy - Borofsky, Michael S.; Gill, Inderbir S.; Hemal, Ashok K.; Marien, Tracy P.; Jayaratna, Isuru; Krane, Louis S.; Stifelman, Michael D. (BJU international, 2013)
What's known on the subject? and What does the study add? There is concern that warm ischaemia time during partial nephrectomy may have an adverse impact on postoperative renal function. As a result, there is increased interest in developing a safe and effective method for performing non‐ischaemic partial nephrectomy. Several novel approaches have recently been described. We present our initial experience performing zero‐ischaemia partial nephrectomy using near‐infrared fluorescence imaging to facilitate super‐selective arterial clamping. We report the operative and early postoperative outcomes from such cases as compared with a matched cohort of patients undergoing traditional partial nephrectomy with clamping of the main renal artery. We show that this technique is both safe and effective and may lead to improved renal preservation at short‐term follow‐up. Objective To describe a novel technique of eliminating renal ischaemia during robotic partial nephrectomy (RPN) using near‐infrared fluorescence (NIRF) imaging. Patients and Methods Over an 8‐month period (March 2011 to November 2011), 34 patients were considered for zero‐ischaemia RPN using the da Vinci NIRF system. Targeted tertiary/higher‐order tumour‐specific branches were controlled with robotic bulldog(s) or neurosurgical aneurysm micro‐bulldog(s). Indocyanine green dye was given, and NIRF imaging used to confirm super‐selective ischaemia, defined as darkened tumour/peri‐tumour area with green fluorescence of remaining kidney. Matched pair analysis was performed by matching each patient undergoing zero‐ischaemia RPN (n = 27) to a previous conventional RPN (n = 27) performed by the same surgeon. Results Of 34 patients, 27 (79.4%) underwent successful zero‐ischaemia RPN; seven (20.6%) required conversion to main renal artery clamping (ischaemia time <30 min) for the following reasons: persistent tumour fluorescence after clamping indicating inadequate tumoral devascularization (n = 5), and parenchymal bleeding during RPN (n = 2). Matched‐pair analysis showed comparable outcomes between cohorts, except for longer operating time (256 vs 212 min, P = 0.02) and superior kidney function (reduction of estimated glomerular filtration rate (−1.8% vs −14.9%, P = 0.03) in the zero‐ischaemia cohort. All surgical margins were negative. Conclusions In this pilot study, we show that zero‐ischaemia RPN with NIRF is a safe alternative to conventional RPN with main renal artery clamping. Eliminating global ischaemia may improve functional outcomes at short‐term follow‐up.